ANALYSIS OF READING CAPABILITIES CLASS IV ELEMENTARY SCHOOLS WITH SCANNING TECHNIQUES - Fitriana Dwi Wijayanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Low reading skills, preferably reading students, a family environment that has never accustomed to a culture of reading and the development of increasingly sophisticated technologies, such as cell phones, usually children prefer the main game on cellphones to read and increase motivation. The point must be instilled in you who are reading is one means to improve the quality of self because by reading someone will get a lot of information. the purpose of receiving support through this research is to describe the reading skills of grade IV students with scanning techniques in Pelita Jaya Elementary School. The place of research is Pelita Jaya Cluster Elementary School consisting of 8 schools with a total of 274 students and a sample of 163 students. This type of research uses quantitative descriptive research with test instruments. The results of this study were the ability to read by scanning techniques from 163 students who became a sample that received students who received very good categories for 31 people, 32 good categories, then only 19 people were categorized, and 81 people were categorized less than 81 people. support the number of classified as sufficient, with an average value of 55.92